1994
DOI: 10.1126/science.7910982
|View full text |Cite
|
Sign up to set email alerts
|

De Novo and Inherited Deletions of the 5q13 Region in Spinal Muscular Atrophies

Abstract: Spinal muscular atrophies (SMAs) represent the second most common fatal autosomal recessive disorder after cystic fibrosis. Childhood spinal muscular atrophies are divided into severe (type I) and mild forms (types II and III). By a combination of genetic and physical mapping, a yeast artificial chromosome contig of the 5q13 region spanning the disease locus was constructed that showed the presence of low copy repeats in this region. Allele segregation was analyzed at the closest genetic loci detected by marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
195
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(207 citation statements)
references
References 20 publications
11
195
0
1
Order By: Relevance
“…Because of the incidence of SMA (homozygous deletion of SMN1) in the Swedish population is around 1 in 12 000 live births, 15 the frequency of heterozygous SMN1 deletions in Sweden can be estimated to be around 1/55, similar to what has been reported in France. 16 The frequency of heterozygous SMN1 deletions found in the Swedish population in this study was in accordance with those reports, suggesting that our control population was representative of the Swedish population as a whole. These lack of association between ALS and SMN1 gene copy number is in contrast to results in French and Dutch cohorts in which abnormal copy numbers of SMN1 have been associated with an increased risk of ALS.…”
Section: Discussionsupporting
confidence: 93%
“…Because of the incidence of SMA (homozygous deletion of SMN1) in the Swedish population is around 1 in 12 000 live births, 15 the frequency of heterozygous SMN1 deletions in Sweden can be estimated to be around 1/55, similar to what has been reported in France. 16 The frequency of heterozygous SMN1 deletions found in the Swedish population in this study was in accordance with those reports, suggesting that our control population was representative of the Swedish population as a whole. These lack of association between ALS and SMN1 gene copy number is in contrast to results in French and Dutch cohorts in which abnormal copy numbers of SMN1 have been associated with an increased risk of ALS.…”
Section: Discussionsupporting
confidence: 93%
“…These events can cause mutations leading to genetic disease (1)(2)(3). Human chromosome 5 contains such an area at 5q13-14, where the abundance of low-copy repeats has been well documented (4)(5)(6)(7)(8)(9). Interestingly, the gene for spinal muscular atrophy (SMA) has been mapped in tight linkage to this region (10,11).…”
mentioning
confidence: 99%
“…12,[33][34][35] In contrast, we detected a de novo mutation event by contrasting phased-SNP haplotypes to SMN1 dosages determined by qPCR and examining the segregation pattern of the haplotype and mutation in additional close relatives. The segregation of the haplotype and SMN1 deletion in this family indicated that the event occurred during a paternal meiosis, as in most other de novo SMN1 deletions.…”
Section: Discussionmentioning
confidence: 99%